The Maine Economic Conversion Project: Promoting a Sustainable Future - Schweppe, Susie; Karvonides, Nicholas (Maine Policy Review, 1994)
For the past five years, a small, but dedicated group of Mainers has been working on the perplexing and sometimes controversial issue of defense conversion. The Portland-based Economic Conversion Project (ECP), an initiative of the Maine Peace Fund, sees opportunity in the nation’s defense downsizing efforts where others see only adversity. Among other goals, the private, non-profit ECP wants to create a sustainable economy that is more responsive to public need than to the disintegrating military industrial complex. Susie Schweppe and Nicholas Karvonides of ECP recently discussed with Maine Policy Review the status of their project and the challenges confrontingMaine and the nation as a result of declining federal defense spending.
Keywords: Maine; defense conversion; economic development